(untitled) (International Journal of Food and Nutritional Sciences, 2022)
To guarantee that students can find work after graduation, it is essential that academic programmes meet the needs of businesses. In order to close the skills gap between employers and Rashtrasant Tukadoji Maharaj Nagpur University’s Master of Computer Applications (MCA) students, this research looks at new ways of teaching computer science. The study examines the efficacy of several training techniques in improving students’ employment preparedness via a mixed-methods approach, which includes surveys and interviews. Personalised learning, service learning, and gamification are some of the approaches that MCA students are most interested in, and this research looks at their effects on skill development and employability. The study also looks at possible roadblocks to new training techniques’ acceptance and offers solutions to such problems. Educational institutions and industry stakeholders may get significant insights from this research on how to improve the employability of MCA graduates. It explains how unique training strategies can close the industry-student gap.